MIDDLE CAMBRIAN HIGH MAGNETIC REVERSAL FREQUENCY (KULUMBE RIVER SECTION, NORTHWESTERN SIBERIA) AND REVERSAL BEHAVIOUR DURING THE EARLY PALAEOZOIC - Pavlov V.; Gallet Y. (My University, 2001)
We present a magnetostratigraphic study of Middle Cambrian sediments along the Kulumbe river (northwestern Siberia). The deposits are V850 m thick and lie within the Mayan stage as constrained by trilobite fossils. Palaeomagnetic analyses reveal two magnetic components. The first component, parallel to the direction of the present day field at the site, is isolated in the low to middle temperature range. A high temperature component (HTC) is then isolated up to 580 or 680³C, carried either by magnetite and/or by hematite. The HTC defines a sequence of 28 magnetic polarity intervals, some of them being defined by only one sample. Considering that the studied section has a duration of V5 Myr, we propose that the magnetic reversal frequency was high (V4^6 reversals per Myr) during part of the Middle Cambrian, among the highest values known within the Phanerozoic. The reversal frequency may have been roughly similar during the Lower Cambrian. We further suggest a drastic decrease of the magnetic reversal frequency between the Lower^Middle Cambrian and the end of the Tremadoc (Ordovician) when a superchron probably occurred. However, this behaviour is still challenged by other scenarios which depend on the chosen Early Palaeozoic time scale and on the reliability of some magnetostratigraphic data.
Keywords: Cambrian; sediments; Kulumbe river; Siberia; Paleozoic::Cambrian; Палеозой::Кембрийская